Evidences for a large hot spot on the disk of Betelgeuse (α Ori). Issue Volume 9:Issue S307(2014) (23rd January 2015) - Montargès, M.; Kervella, P.; Perrin, G.; Chiavassa, A.; Le Bouquin, J. B.
Abstract: Massive evolved stars contribute to the chemical enrichment of the Galaxy. When they die as supernova but also through their mass loss during the several thousands of years of their red supergiant (RSG) phase. Unfortunately the mass loss mechanism remains poorly understood. Detailed study of the CSE and photosphere of nearby RSGs is required to constrain this scenario. Betelgeuse is the closest RSG (197 pc) and therefore has a large apparent diameter ( 42 mas) which makes it a very interesting target. For several years, our team has lead a multi-wavelength and multi-scale observing program to characterize its mass loss. We will review here our recent results in near-infrared interferometry.